Editorial - Balloni A. (Rivista di Criminologia, Vittimologia e Sicurezza, 2017)
In this issue Roberta Bisi made a commitment to further explore some aspects of the Cogne case which has already been addressed in a previous issue of this Journal. Indeed, the aim of the review of Cogne case psychodiagnostic investigations is to analyse the important role of the algorithm in terms of controlling and predicting human behaviour.